Examining access to addiction treatment: Scheduling processes and barriers - Quanbeck, Andrew (2012)
This paper reports on the phone scheduling systems that patients encounter when seeking addiction treatment. Researchers made a series of 28 monthly calls to 192 addiction treatment clinics to inquire about the clinics’ first available appointment for an assessment. Each month, the date of each clinic’s first available appointment and the date the appointment was made were recorded. During a 4-month baseline data collection period, the average waiting time from contact with the clinic to the first available appointment was 7.2 days. Clinics engaged in a 15-month quality improvement intervention in which average waiting time was reduced to 5.8 days. During the course of the study, researchers noted difficulty in contacting clinics and began recording the date of each additional attempt required to secure an appointment. On average, 0.47 callbacks were required to establish contact with clinics and schedule an appointment. Based on these findings, aspects of quality in phone scheduling processes are discussed. Most people with addiction seek help by calling a local addiction treatment clinic, and the reception they get matters. The results highlight variation in access to addiction treatment and suggest opportunities to improve phone scheduling processes.